An Appraisal Of Children’s Right And Child Domestic Servants Under Child Rights Act 2003 - Dankadai, Lubabatu Bello (Advances in Social Sciences Research Journal, 2015)
This article explores the issue of domestic child service as specie of the worst forms of exploitative child labour affecting children in the form of physical, mental, psychological and economic trauma, that parents force their children in to, without any legal justification, under the most deplorable conditions to supplement their family income. Domestic child Labour as one of the forms of such exploitation has many negative effects on our children, because many of them are exposed to physical, emotional and sexual exploitations as well as denied full educational opportunities. In Nigeria today issue of domestic child service have become one of the most prominent and prevalent forms of child labour practice among the households, children especially girls aged five, and above and mostly ten and thirteen years are trafficked from rural areas to the urban cities to serve as domestic servants. This practice has become a great problem, because it directly affects and interferes with so many children’s rights provided under the law as well as the overall physical, mental and moral development of such children. This paper analyzes this turbulent issue of domestic child labour and focuses on the examination and appraisal of the relevant children’s rights provided under Child’s Rights Act (2003) which the practice interferes with. In the end the paper will provide solutions based on the findings of this paper, which could particularly enhance the rights of the vulnerable children involved in child domestic service in Nigeria.